Serum Cu, Mn and Zn Levels and Oxidative Stress in Cattle Performing Tongue-playing - Kirmizigul, Ali Haydar; Ozcelik, Mehtap; Ogun, Metin; Erkilic, Ekin Emre; Paksoy, Nilgun; Merhan, Oguz; Uzlu, Erdogan (Kafkas Univ, Veteriner Fakultesi Dergisi, 2019)
This study was aimed at determining serum copper (Cu), manganese (Mn) and zinc (Zn) levels and the occurrence of oxidative stress in cattle performing tongue-playing stereotypies. The study material comprised of 25 healthy cattle and 50 stereotypic cattle performing tongue-playing, which were of a varying age and sex composition. The stereotypic animals were observed to display non-physiological tongue movements either by raising their heads and stretching their tongue out at long or short time intervals, or by contorting, rolling or swinging their tongue and making circular tongue movements in their mouth. These animals were confirmed to perform tongue-playing stereotypies. 10 mL blood samples were taken from each animal included in the study, and the sera extracted were analysed for serum Cu, Mn, Zn, malondialdehyde (MDA), nitric oxide (NO), total oxidant status (TOS) and total antioxidant status (TAS) levels. While the serum Mn levels of the stereotypic animals were lower than those of the healthy animals (P<0.001), it was observed that the serum Cu and Zn levels of the stereotypic and healthy animals did not differ (P>0.05). While the MDA (P<0.001), NO (P<0.001) and TOS (P<0.05) levels of the stereotypic animals were found to be higher than those of the healthy animals, the TAS (P>0.05) levels did not differ between the two groups. In result, it was concluded that Mn deficiency has an important role in the aetiology of tongue-playing stereotypies, and that this behavioural disorder is associated with oxidative damage or inflammation. Oxidative stress in tongue playing disease is thought to be formed due to cellular damage or stress.
Dil oynatma hastalığı olan sığırlarda serum cu, mn, zn seviyeleri ve oksidatif stres
International Turkish Veterinary Internal Medicine Congress -- OCT 10-13, 2017 -- Antalya, TURKEY
Keywords: Cattle; Copper; Manganese; Zinc; Tongue-playing; Malondialdehyde; Nitric oxide Total oxidant status; Total antioxidant status